Chapter Dante epilettico, o anche isterico. Una storia psichiatriico letteraria di fine Ottocento - ARTIFONI, Enrico (Reti Medievali E-Book, 2021)
In the last decade of the 19th century psychiatric sciences in Italy proposed many psychopathological interpretations of exceptional personalities. An important role was played by the psychiatrist Cesare Lombroso with his books on genius and madness, which inspired other similar research. The case of Dante Alighieri, on whom Lombroso made a diagnosis of epilepsy, is part of this context. The article analyses the main texts (for and against) of this psychiatric-literary affair and clarifies the role of the French doctor Max Durand-Fardel, from whom Lombroso said he took the cue for his diagnosis of epilepsy.